Popular markets, flow of goods and illegalisms in Posadas / Argentina (Terr@ Plural, 2020)
This paper aims to analyze the relations between attempts to control the commercialization of goods transported and traded by workers in the popular markets of Posadas, Argentina, exploring the gaps between what is standardized and what is carried out by the different agents involved. For this, observations were made in ‘Mercado La Placita del Puente’ and in ‘Mercado Modelo’, as well as interviews with managers and workers. The results demonstrate the existence of tensions among ‘puesteros, ‘paseras’ and the administrative agents, composed of disputes in the maintenance and the development of strategies that enable the necessary and effective work practices, but also flexibility in the law application, which allows the visualization of a space where different agents articulate, exposing negotiations and resistances.
Keywords: Border; Paseras; Popular Workers; Popular Globalization